Socialno delo z mladimi uporabniki prepovedanih drog - Hren, Jože (Socialno delo, 2024)
The authors present a panoramic overview of programmes, services and various treatments available in Slovenia in social work with young users of illicit drugs. Epidemiologically, cannabis is the most widespread and, in terms of risks, the most underestimated drug used by young people. Thus, in the prevention, reduction and less risky use of this and other drugs, it is crucial that young people have access to support that they can reach out to. A safe environment, acceptance and an equal relationship are essential here. The field of prevention, especially early prevention, has received special attention in Slovenia in recent years and is experiencing significant development. Preventive programmes and interventions can address a wider range of risk factors and forms of vulnerability, such as peer violence, mental health, and strengthen emotional and social protective factors. It is important, however, that there is a wide range of services, including low-threshold ones, which do not make participation conditional on abstinence. Harm reduction programmes, including drug testing, counselling and therapeutic programmes, are measures that can empower and motivate individuals to participate in treatment and long-term recovery. All of the above is important support for the social (re-)integration of particularly vulnerable individuals and social groups, including young illicit drug users.
Keywords: addiction; counselling; drugs; harm reduction; odvisnost; okrevanje; prepovedane droge; prevention; preventiva; recovery; social integration; social work; socialna integracija; socialno delo; svetovanje; zmanjševanje škode